Short-Term Outcomes following Standardized Admission of Late Preterm Infants to Family-Centered Care - Reiss, Jonathan; Upadhyayula, Pavan S.; You, Hyeri; Xu, Ronghui; Stellwagen, Lisa M. (American Journal of Perinatology, 2019)
Objective The study compares the short-term outcomes of late preterm infants (LPI) at an academic center in San Diego, California after a change in protocol that eliminated a previously mandatory 12-hour neonatal intensive care unit (NICU) observation period after birth.Study Design This is a retrospective observational study examining all LPI born with gestational age 35 to 366/7 weeks between October 1, 2016 and October 31, 2017. A total of 189 infants were included in the review. Short-term outcomes were analyzed before and after the protocol change.Results Transfers to the NICU from family-centered care (FCC) were considerably higher (23.2%) following the protocol change, compared to before (8.2%). More infants were transferred to the NICU for failed car seat tests postprotocol compared to preprotocol. Length of stay before the protocol change was 5.13 days compared to 4.80 days after.Conclusion LPI are vulnerable to morbidities after delivery and through discharge. We found an increase in failed car seat tests in LPI cared for in FCC after elimination of a mandatory NICU observation after birth. The transitions of care from delivery to discharge are key checkpoints in minimizing complications.
Keywords: late preterm infant; neonatal intensive care unit admission; car seat test; transitions of care; baby friendly hospital